Determining the tactical and technical level of competitive tennis players using a competency model: a systematic review - Miguel Crespo; Rafael Martínez-Gallego; Ales Filipcic (Frontiers Media S.A., 2024)
IntroductionThe aim of this systematic review is to provide an evidence-based synthesis of the literature on the topic of technical and tactical competencies of tennis players and to answer the following research questions: (1) What is the state of the art of research on technical and tactical competencies (i.e., skills and knowledge) and tennis; (2) What are the most important topics related to technical and tactical competencies in tennis players.MethodsElectronic searches were conducted in Web of Science, PubMED and SPORTDiscus (August to September 2023). This systematic review was conducted in accordance with PRISMA guidelines. To reduce risk, all published literature was searched and primary studies were included. The search terms included skills or competencies, match or play, player and tennis and excluded studies on non-competitive tennis players-notation analysis, AI method, systematic review and validation of tools.Results and discussionOf the 390 publications found in these searches, 13 articles were considered relevant and included in this study. They were divided into three categories: (1) technical-tactical skills, (2) match situations and (3) match performance. There was clear evidence that there is a test instrument for analyzing tactical-technical skills that has sufficient reliability and validity and is of practical value to tennis coaches. The development of tactical-technical skills is influenced by method (variability between/within skills), conditions (court size, ball type) and areas of development (situational awareness, anticipation, decision making). There are differences in match and stroke performance between different quality groups (professionals, juniors), which can also be influenced by mental strength. For a comprehensive study of tennis players' abilities, the use of modern technologies is possible and necessary in the future. Future research should focus on the creation of competency models for the playing level of tennis players, which could include at least three key elements: (1) key competencies, (2) description of standards, (3) evidence.